An analysis of corporate income tax avoidance criminalization within the European Union - Šķupele, Kitija (Riga Graduate School of Law, 2020)
Several studies have reported that tax avoidance is used mostly by multinational companies where, by structured schemes and jurisdiction arbitrage, profits are shifted. Consequently, no or little taxes on significant incomes are paid at Member State’s budget. Such intentional tax liability minimization practice should not be allowed, and effective measures, such as penalties, should be provided. Solving the global issue, Organization for Economic Co-operation and Development cooperating with the European Union have created an anti-tax avoidance framework which provides essential changes in existing Court of Justice of European Union interpretation methods and existing rules. Accordingly, the primary goal of this thesis is to analyse the European Union measures already taken to address tax avoidance issues with the intention to understand whether the new anti-tax avoidance framework would comply with existing anti-abuse practice. The economic and behavioural perspective will be taken into account determining the potential loss to society. Furthermore, possible challenges and recommendations deriving from Anti-tax avoidance Directive and Common Corporate tax base harmonization will be indicated, underlying efficiency of penalties.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Taxation